2012
DOI: 10.1080/02640414.2012.701761
|View full text |Cite
|
Sign up to set email alerts
|

Developmental activities and the acquisition of superior anticipation and decision making in soccer players

Abstract: We examined whether soccer players with varying levels of perceptual-cognitive expertise can be differentiated based on their engagement in various types and amounts of activity during their development. A total of 64 participants interacted with lifesize video clips of 11 versus 11 dynamic situations in soccer, viewed from the first-person perspective of a central defender. They were required to anticipate the actions of their opponents and to make appropriate decisions as to how best to respond. Response acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 25 publications
8
89
0
5
Order By: Relevance
“…The results revealed that skilled players are more accurate in anticipating opponents' actions and, consequently, in deciding on the more appropriate course of action than less-skilled players. The findings of this study corroborated those from a previous study of the same first author [1,11] as well as from Ward and Williams [8].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The results revealed that skilled players are more accurate in anticipating opponents' actions and, consequently, in deciding on the more appropriate course of action than less-skilled players. The findings of this study corroborated those from a previous study of the same first author [1,11] as well as from Ward and Williams [8].…”
Section: Discussionsupporting
confidence: 83%
“…Assessment procedures within this model were the same as those of the previous model. One study investigated the influence of activities performed during their development on anticipation skills [1]. In this study, the duration of soccer practice and soccer-related activities was analysed and its aim was to identify the contribution of each of these variables in the development of perceptual-cognitive processes such as anticipation and decision-making.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations